Urgensi Pendampingan dalam Upaya Peningkatan Manajerial Usaha Mikro dan Usaha Kecil - Irawan, Dandan (JURNAL KEBANGSAAN, 2018)
The existence of micro businesses and small businesses in Indonesia currently dominates businesses, with a total of more than 99% of the total business operators in Indonesia. These micro and small scale scale business actors make a very significant contribution in encouraging the Indonesian economy. In its implementation, it is always encouraged to continue to pay attention to business performance continuously. This can be realized if appropriate assistance is provided, where the basis of assistance is egalitarian or equality of position so that assistance is expected to improve managerial skills for business people. Through the essence of mentoring, it is expected that improving management quality is expected to create a transfer of knowledge in terms of more efficient and prospective business management experience for MSMEs and will obtain continuity of production or increase greater capacity. Keywords: Assistance, Business Managerial.